Energetic cost of predation: Aerobic metabolism during prey ingestion by juvenile rattlesnakes, Crotalus durissus - Cruz-Neto, Ariovaldo P. [UNESP]; Andrade, Denis V. [UNESP]; Abe, Augusto Shinya [UNESP] (JSTOR, 1999)
We investigated the cost of prey ingestion in the South American rattlesnake, Crotalus durissus, to see if the capacity to generate energy aerobically could be a constraint on the size of the prey that can be ingested. To accomplish this goal, we measured time and aerobic metabolism (inferred from oxygen consumption) of juvenile C. durissus ingesting prey ranging from 10 to 50% of their own body mass. Time needed for prey ingestion increased with prey size, with prey representing 10 and 20% of snake size being ingested with the same effort. Whole animal rates of oxygen consumption increased linearly with prey size, but at a slower pace for snakes ingesting prey larger than 30% of their body mass. Aerobic factorial power input necessary for prey ingestion increased with prey size, and for snakes ingesting prey representing 50% of their body mass it equaled the aerobic factorial scope for exercise. For the maximum prey size tested, the aerobic derived energy necessary for prey ingestion represented 0.02% of the total energy content of the prey. Within the prey size range we studied, the cost of ingestion did not constitute any constraint on the size of the prey that can be ingested. These constraints are set by morphological (gape size), ecological (predation risk), and, probably, by physiological parameters, as suggested by the tendency of V̇O2 during ingestion to increase at a slower pace at relative larger prey sizes.
Keywords: Crotalus durissus